Double‐Side Crystallization Tuning to Achieve over 1 µm Thick and Well‐Aligned Block‐Like Narrow‐Bandgap Perovskites for High‐Efficiency Near‐Infrared Photodetectors. (29th April 2021) - Liu, Hui; Zhu, Hugh Lu; Wang, Zishuai; Wu, Xiao; Huang, Zhanfeng; Huqe, Md Rashedul; Zapien, Juan Antonio; Lu, Xinhui; Choy, Wallace C. H.
Abstract: Solution‐processed narrow‐bandgap Sn–Pb perovskites have shown their potential in near‐infrared (NIR) photodetection as a promising alternative to traditional silicon and inorganic compounds. To achieve efficient NIR photodetection, high‐quality Sn–Pb perovskite thick films with well‐packed, smooth, and pinhole/void‐free features are highly desirable for boosting the spectral absorption. Understanding the crystallization kinetics and tuning the crystallization are fundamentally important to reach such high‐quality thick Sn–Pb perovskite films, and have been limitedly explored. Herein, an approach of double‐side crystallization tuning through low‐temperature space‐restricted annealing in methylammonium‐free Sn–Pb perovskite films with over 1 µm thickness is proposed. More specifically, through simultaneously retarding the crystallization in the top of precursor films and promoting the crystal growth of the bottom of precursor films, high‐quality and block‐like thick FA0.85 Cs0.15 Sn0.5 Pb0.5 I3 perovskite films with improved crystallinity, preferred out‐of‐plane orientation, and reduced trap density are achieved. Finally, photovoltaic‐mode Sn–Pb perovskite NIR photodetectors show a high external quantum efficiency of ≈80% at 760–900 nm, a recorded responsivity of 0.53 A W −1, and a high specific detectivity of 6 × 10 12  Jones at 940 nm. This study offers the fundamental understanding of the crystallization kinetics of thick perovskite films and paves the way for perovskite‐based emerging NIR photodetection and imaging applications. Abstract : High‐quality Sn–Pb perovskite thick films with well‐packed, smooth, and pinhole/void‐free features are formed via double‐side crystallization tuning with a low‐temperature space‐restricted annealing process. The fabricated near‐infrared photodetectors show a high and flat external quantum efficiency of ≈80% at 760–900 nm, remarkable responsivity of 0.53 A W −1 and high specific detectivity of 6 × 10 12  Jones at 940 nm.